Risk factors for persistence of asthma in children: 10-year follow-up. (November 2013) - Aydogan, Metin; Ozen, Ahmet; Akkoc, Tunc; Eifan, Aarif O; Aktas, Esin; Deniz, Gunnur; Gocmen, Izlem; Bahceciler, Nerin N.; Barlan, Isil
Abstract Objective: Risk factors related to the outcome of childhood asthma are not yet well established. We aimed to investigate the long-term outcome for children with asthma to determine the risk factors in predicting persistence of disease. Methods: Sixty-two children with asthma were evaluated retrospectively at the end of a 10-year follow-up. Patients were asked to complete a questionnaire requesting clinical information, and underwent physical examination, skin prick testing, a pulmonary function test and bronchial provocation testing. Immunologic parameters evaluated were allergen-specific IgE and IgG4 levels, and allergen-induced generation of CD4+CD25+ cells. Results: Mean age at final assessment was 15.9 ± 3.6 years, and duration of follow-up was 10.30 ± 1.27 years. Fifty percent of patients outgrew their asthma during the 10-year follow-up period. All the non-atopic patients outgrew their disease during the study period, whereas 67% of atopic patients did not. We identified two risk factors independently related to the persistence of symptoms: presence of bronchial hyper-responsiveness and presence of rhinitis. Atopic children who were in remission demonstrated significantly higher allergen-induced CD4+CD25+ T cells compared to healthy controls. Conclusions: Atopy, presence of rhinitis, positive and presence of bronchial hyper-reactivity are important risk factors for the persistence of asthma in children. Allergen-induced CD4+CD25+ T cells were higher in the atopic children who outgrew their disease, implicating an immunological mechanism of asthma remission in children.